UJI KELAYAKAN MODUL PEMBELAJARAN ADOBE PHOTOSHOP CS6 SEBAGAI SUMBER BELAJAR UNTUK SMK KOMPETENSI KEAHLIAN MULTIMEDIA KELAS X - Handika Asep Kurniawan (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2021)
This research aims to produce a learning modules of Adobe Photoshop CS6 and determine how feasible is the learning modules for vocational schools especially class X in multimedia competence. The research design used was based on the ADDIE development model which includes five steps, namely Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), Evaluation (Evaluation). The type of data used was quantitative and qualitative. The data was collected by questionnaire. Techniques of data analysis in this research is descriptive quantitative. The results showed that: 1) The development steps of Adobe Photoshop CS6 module is conform with the ADDIE development model with five basic stages undertaken in the development of Adobe Photoshop CS6 learning modules are: (1) Analysis (Analysis), (2) Design (Design), (3) Development (Development), (4) Implementation (Implementation), (5) Evaluation (Evaluation). 2) Based on the material expert assessment, the feasibility of the learning module covering aspects completeness of the content, language, presentation, and graphic has been achieved with a percentage of 86.34% (very decent). Based on the media expert assessment, the feasibility of the learning module covering aspects completeness of the display module design, ease of use, consistency, format, usefulness, and graphic has been achieved with a percentage of 84.52% (very decent). Based on the module test which was conducted to 3 schools those are SMK Negeri 2 Yogyakarta, SMK Negeri 3 Yogyakarta and SMK Negeri 7 Yogyakarta involving 107 students, the average values ​​obtained with a percentage of 84.30% 147.52 (very decent).